Dynamics of Causality between Real Estate and Stock Prices: Evidence from Türkiye - Evrim Turgutlu; Pınar Narin Emirhan (Ekonomi, Politika & Finans Araştırmaları Dergisi)
This paper aims to examine the causal relationship between real estate and stock prices in Türkiye over the 2010-2023 period and uncover whether the wealth effect or the credit price effect has been dominant. This study investigates the association between real estate prices and stock prices in Türkiye using both linear and non-linear ARDL cointegration models. A recently developed non-linear ARDL technique by Shin, Yu, and Greenwood-Nimmo (2014) is employed to investigate possible asymmetric relationships between real estate and stock prices. Linear ARDL bounds test results indicate strong evidence of wealth effect for Türkiye. The findings of the non-linear ARDL technique reveal that there is a strong asymmetric association between real estate and stock prices in Türkiye and there is evidence of the existence of both wealth and credit price effects. The asymmetric association is more dominant in the credit price effect model. The findings of the study will help both investors and policymakers to establish effective policies for developing portfolios considering the asymmetric associations and provide a better understanding of the driving forces behind real estate prices.